Central do pet: uma plataforma web para unificar e divulgar informações sobre cães e gatos - Fernandes, Alescia Bezerra (Universidade Federal Rural do Semi-Árido, 2018)
The abandonment of animals is an everyday problem: besides being a cruel act, it can bring complications to society. When they are abandoned, the animals begin to live in poor conditions, with fear, going hungry, thirsty, becoming vulnerable to maltreatment and diseases, and even risking the quality of public health. In view of this scenario, the objective of this monograph is to create a free collaborative web tool about abandoned animals, in order to aggregate information about these animals and to facilitate communication on issues such as donations, adoption and dissemination of campaigns / events, all in favor of reducing the number of abandoned animals. To do so, a survey was carried out on the characteristics of the animals that the tool should cover and on the already existing technologies and tools, considering their strengths and weaknesses. From this, the Central do Pet was developed, which consists of a collaborative environment for adopters, NGOs, ZCCs, public entities and any other that shows interest in the abandonment of animals. In the study, it was possible to perceive that the abandonment of animals is not a problem that will be resolved quickly and the Central do Pet is expected to act as a device to decrease the rates of abandonment. In the future, functionalities may be added to cover other areas of interest to pet owners, such as veterinary services, information on animal care, location of pet shop and hotel services, among others that may be of interest to the target audience.
Monografia
Keywords: Central do pet; Adoção de animais; Ferramenta web; Central do pet; Pets adoption; Web tool; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA